The The Objectives of Moral Education on Islamic View : - - Suryadi, Rudi Ahmad; Asy’ari, Asy’ari; Latipah, Euis (East Asian Journal of Multidisciplinary Research, 2024)
Humans in the view of Islam have good innate potential. In the view of Islam, this potential is called fithrah.  Humans since being born already have the potential for good and kindness. But in living his life, when humans relate to something outside themselves, due to environmental influences, humans who previously had good potential, became bad behavior and had bad morals.. The research used a qualitative approach with a literature study method. The research findings is moral education simply has the aim of improving student behavior and instilling it deeply so that the urge to have good behavior remains embedded in him. Humans have good innate potential (fithrah). Education as an effort to humanize humans is carried out to deliver humans to be as before, in a good state. Humans who return to the state of fithrah are humans with good morals. The process of moral education has the aim that humans become good human beings. In praxis, educational institutions not only prepare students to have certain intelligence and skills. Creating a good relationship between individuals and their God, both sirri (secretly) and a'lany (openly), makes individuals istikamah close to Allah Swt as if they see Him, feel His presence, and are sincere in worship.